2022
DOI: 10.2186/jpr.jpr_d_20_00082
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of maxillary premolars restored with different endocrown designs and materials after artificial ageing

Abstract: Purpose: To evaluate the effect of three different designs and two monolithic ceramic materials on the durability and fracture resistance of endocrowns on maxillary first premolars, in comparison to post-and-core crowns. Methods: Fifty-six maxillary premolars were endodontically treated and shortened to a level of 2 mm from the cervical line, and randomly categorized into six endocrown groups and post-and-core crown control group (n=8); E1; endocrowns with flat occlusal table (without ferrule), E2; endocrowns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 56 publications
4
59
0
Order By: Relevance
“…Another research implies our findings by Ahmed et al who reported that the design with circumferential ferrule preparation increased fracture values for the two different treating modalities (post, core, crown and endocrown) with two different ceramic materials (zirconia and lithium disilicate) [37] .…”
Section: Discussionsupporting
confidence: 86%
“…Another research implies our findings by Ahmed et al who reported that the design with circumferential ferrule preparation increased fracture values for the two different treating modalities (post, core, crown and endocrown) with two different ceramic materials (zirconia and lithium disilicate) [37] .…”
Section: Discussionsupporting
confidence: 86%
“…4 , higher stresses were observed in the cervical margin area of the shoulder margin compared with the flat joint margin; this might significantly increase the risks of the debonding of the restoration. In addition, clinical studies have revealed some difficulties during the fabrication of endocrown with shoulder margin, owing to the limited milling area between the pulpal inlay and proximal axial ferrule walls [ 41 ]. As such, the butt joint margin presents better protection of the adhesive interface and restoration from detachment.…”
Section: Discussionmentioning
confidence: 99%
“…16 Conducting thermal and dynamic mechanical loading prior to the fracture resistance test is considered clinically relevant as it might significantly reduce the fracture resistance of ceramic retorations. 17,18 Only one previous study 19 subjected lithium disilicate endocrowns to high thermomechanical cycling combining 5000 thermal cycles and a 1.2 million dynamic loading cycles imitating 5 years of clinical service. 20 However this latter study was performed on premolar teeth.…”
Section: Discussionmentioning
confidence: 99%